Virtual taphonomy: A new method integrating excavation and postprocessing in an archaeological context. Issue 2 (26th February 2015) - Wilhelmson, Helene; Dell'Unto, Nicoló
ABSTRACT The objective of this paper was to integrate excavation and post‐processing of archaeological and osteological contexts and material to enhance the interpretation of these with specific focus on the taphonomical aspects. A method was designed, Virtual Taphonomy, based on the use and integration of image‐based 3D modeling techniques into a 3D GIS platform, and tested on a case study. Merging the 3D models and a database directly in the same virtual environment allowed the authors to fully integrate excavation and post‐processing in a complex spatial analysis reconnecting contexts excavated on different occasions in the field process. The case study further demonstrated that the method enabled a deeper understanding of the taphonomic agents at work and allowed the construction of a more detailed interpretation of the skeletal remains than possible with more traditional methods. The method also proved to add transparency to the entire research process from field to post‐processing and interpretation. Other benefits were the timesaving aspects in documentation, not only in the excavation process but also in post‐processing without creating additional costs in material, as the equipment used is available in most archaeological excavations. The authors conclude that this methodology could be employed on a variety of investigations from archaeological to forensic contexts and add significant value in many different respects (for example, detail, objectivity, complexity, time‐efficiency) compared to methods currently used. Am J Phys Anthropol 157:305–321, 2015. © 2015 Wiley Periodicals, Inc.